2019
DOI: 10.17102/cnr.2019.02
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Abundance of Bees and Wasps (Hymenoptera: Aculeata) in North Central Bhutan

Abstract: Bees and wasps (Aculeata: Hymenoptera) are group of insects which plays important roles in agriculture and are economically valuable species. The occurrence of these species depends on the climatic and non-climatic factors. This paper documents the bee and wasp diversity and their distribution based on the altitudinal gradient and land use in the Bumthang and Trongsa dzongkhags. The data were collected using opportunistic visual encounter and transect walk method over a period of eight months from September, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Although some amphibians are relatively tolerant and able to survive in acidic environments, studies have demonstrated that low pH can lead to increased mortality among species that are sensitive to acidic water, resulting in decreased hatching success and negatively affecting amphibian growth and development (Gosner & Black, 1957; Pierce, 1985). As a result, some species of amphibians can be more abundant in aquatic environments with a more alkaline or neutral, pH (Tenzin & Dhendup, 2017). We observed a negative relationship between the detectability of C. gaudichaudii and pH, with a higher probability of detection at lower pH levels.…”
Section: Discussionmentioning
confidence: 99%
“…Although some amphibians are relatively tolerant and able to survive in acidic environments, studies have demonstrated that low pH can lead to increased mortality among species that are sensitive to acidic water, resulting in decreased hatching success and negatively affecting amphibian growth and development (Gosner & Black, 1957; Pierce, 1985). As a result, some species of amphibians can be more abundant in aquatic environments with a more alkaline or neutral, pH (Tenzin & Dhendup, 2017). We observed a negative relationship between the detectability of C. gaudichaudii and pH, with a higher probability of detection at lower pH levels.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates the low suitability of the area for nesting causing altitudinal variation in the distribution of nests. Although high altitude can have diverse and rich bee species (Tenzin and Katel, 2019), abundance and species richness decline at increasing altitudes (Hoiss et al, 2012;Karunaratn and Edirisinghe, 2009). Interestingly, Figuera (2020) reported an increasing trend in bee diversity with increasing altitude but stressed the distinctive difference in community structure along the elevation gradient.…”
Section: Altitudinal Distribution Of Bee Nestsmentioning
confidence: 99%
“…With this new addition, Bhutan now has 126 fish species (DoFPS studies of Bhokta & Solanki (2020) was also referred for confirmation. Meanwhile, the specimen was collected and euthanized using 0.001 percent clove oil and treated in 10% formalin for fixation as per Gurung et al (2012) and Tenzin & Dhendup (2017) and it is currently deposited in the Laboratory of the Southern Wildlife Rescue and Rehabilitation Centre (SWRRC) in Sarpang District. Fin formula is the key feature been used for identification and comparison as tabulated (Table 1).…”
mentioning
confidence: 99%